Growth performance of Tectona grandis in the western Terai of Nepal - Thapa, H.B.; Gautam, S.K. (Banko Janakari, 2007)
Assessment of growth, biomass and volume of Tectona grandis (teak) was done at a 13-year old plantation established at Shankarnagar, Rupandehi district. Operations such as prunning, prunning and singling, and thinning were carried out at 4, 7.5 and 8.5 years respectively. Diameter increment was 2.3 cm within one year of thinning. Estimated average fresh wood production was 58.8 kg (87.6 tons ha-1) and 29.6 kg (16.1 tons ha-1) in thinned trees and 75.5 kg (71.4 tons ha-1) for trees after thinning. Likewise green leaf production was 5.1 kg tree-1 (7.5 tons ha-1). Above ground green biomass was 32.6 kg tree-1 (17.7 tons ha-1) for thinned trees, 63.9 kg tree-1 (95.1 tons ha-1) for trees before thinning and 81.9 kg tree-1 (77.2 tons ha-1) for trees after thinning. The mean over bark stem volume was 0.0707 m3. In thinning, 21 m3 per ha-1 volume was removed. The volume of standing trees before thinning at 7.5 years was 105.2 m3 ha-1. After thinning, per unit and mean basal area, biomass and over bark stem volume has increased considerably during 4-years from 7.5 years to 11.5 years. This rotation period could be applied for future plantations and already established teak plantations on good sites in the Terai / Inner Terai of Nepal to supply the wood for veneer and small timbers. Key words: Tectona grandis, growth, biomass, volume, rotation, thinning, Nepal Banko Janakari Vol.15(2) 2005 pp6-12